WOMEN WORKERS AND THEIR ECONOMIC ROLES DURING COVID-19 OUTBREAK FROM AN ISLAMIC PERSPECTIVE: A CASE OF BENTOR DRIVERS IN GORONTALO, INDONESIA - Luqmanul Hakiem Ajuna; Muhammad Amri (Share: Jurnal Ekonomi dan Keuangan Islam, 2021)
The objective of this research is to examine and reveal the impact of the adoption of Large-Scale Social Restrictions (Pembatasan Sosial Berskala Besar - PSBB) in Gorontalo province on the roles of women working as drivers of pedicab motorcycle (Becak Motor – Bentor) in addition to being a housewife. This study is qualitative research that gathered data through interviews with the drivers and related parties. Data were analyzed using a phenomenological approach with a thematic study of the Qur'an and Hadith. The results revealed that the family's economic needs became the main reason for women choosing to be Bentor drivers. The implementation of working hours and quantity controls, as well as the prevalence of staying at home, had decreased their income; however, their household duties were still performed, despite the worst economic conditions. Another fact is that the implementation of PSBB has succeeded in decreasing the introductory reproduction rate (R0) of the transmission of Covid-19. In addition, the Qur'an and Hadith allow women who want to work outside their houses but still follow religious instructions always to protect themselves and their dignity and not to ignore their household duties.==================================================================================================ABSTRAK – Pekerja Perempuan dan Peran Ekonomi Mereka pada Masa Covid-19 Ditinjau dari Perspektif Islam: Kajian pada Supir Bentor di Gorontalo, Indonesia. Penelitian ini bertujuan menganalisa dampak penerapan Pembatasan Sosisal Berskala Besar (PSBB) di Provinsi Gorontalo terhadap peran ganda perempuan berprofesi sebagai supir bentor selain sebagai ibu rumah tangga. Kajian ini merupakan penelitian kualitatif yang mengumpulkan data dari wawancara para supir bentor tersebut dan pihak-pihak terkait lainnya. Data dianalisis dengan pendekatan fenomenologi ditambah dengan kajian Tematik Alqur’an dan Hadis dalam menyusun bahasannya. Hasil penelitian menunjukkan bahwa alasan utama perempuan memilih berperan ganda adalah tuntutan ekonomi keluarga. Pemberlakuan aturan jam dan volume operasi serta adanya himbauan stay at home telah menurunkan pendapatan mereka, sementara tugas rumah tangganya berjalan normal meski kondisi ekonomi berada diposisi terburuk. Fakta lain adalah penerapan PSBB berhasil menurunkan tren angka reproduksi dasar (R0) penularan Covid-19. Sementara Alqur’an dan Hadis tidak melarang perempuan yang hendak bekerja di luar rumah namun dengan tetap mengikuti petunjuk agama untuk senantiasa menjaga diri dan kehormatan serta tidak menyia-nyiakan urusan rumah tangganya.